When Likes Become the Balance Sheet: Digital Folklore, Performative Accountability, and the Politics of Accounting Legitimacy in the Platform Era - Mohd Bahaudin Ihsan; Ahmad Rio L (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study develops a critical conceptual examination of the changing relationship between digital communication, accountability, and legitimacy in contemporary platform environments. Using a non-empirical qualitative design grounded in critical literature synthesis and abductive conceptual interpretation, the study integrates scholarship from accounting, digital culture, legitimacy theory, sustainability reporting, and platform governance to explain how organizational performance is increasingly interpreted through symbolic visibility rather than exclusively through formal reporting mechanisms. The analysis identifies three interconnected transformations. First, accountability increasingly operates performatively through recurring digital narratives, visual formats, and public interaction. Second, legitimacy becomes progressively shaped by symbolic recognition and communicative circulation, producing forms of social validation that may appear persuasive despite limited evidentiary grounding. Third, the expansion of algorithmically mediated visibility creates new tensions between public attention and accounting materiality, generating conditions of reduced auditability and intensified dependence on symbolic indicators. The study proposes a multilayer analytical framework consisting of actor, claim, formula, validation, and verification dimensions to distinguish communicative legitimacy from accountable performance. The article contributes theoretically by extending accounting inquiry toward platform-mediated accountability and contributes methodologically through a conceptual model for interpreting digital reporting practices beyond conventional disclosure frameworks.